Financial Accessibility and Performance of Small and Medium Enterprises in Busia Municipality - Julius Byansi (Uganda Christian University, 2024)
The purpose of the study was to establish the relationship between financial accessibility and performance of SMEs in Busia Municipality. The study was guided by three objectives: to examine the impact credit policy on financial accessibility in Busia Municipality; to establish impact of loan portfolio on financial accessibility in Busia Municipality; and to assess the relationship between financial accessibility and performance of SMEs in Busia Municipality. A cross-section survey research design using both qualitative and quantitative approaches was used. A sample size of 60 participants was determined from a target population of 210 subjects using both simple random sampling and purposive sampling techniques. Data was collected using questionnaire method. Data was analyzed using descriptive (mean and standard deviation). The findings indicate collateral security as the major determinant of financial accessibility. Low investment potential is the major challenge affecting performance of SMEs in Busia municipality. There is a moderate positive and significant relationship between financial accessibility and performance of SMEs financial accessibility contributing as low as 17.4% of the level of performance of SMEs in Busia municipality. The study contributes to the existing knowledge on financial accessibility and performance of SMEs by extending the application of the credit access theory and financial intermediation theory. The study recommended that business owners should venture into investment decision making to elevate their investment potential while Bank of Uganda should come up with policies that flexibly enable SMEs to access financial assistance.